Insights on innovation and technology management curriculum in public universities in Turkey - AŞKUN, OLCAY BİGE (BILGESEL YAYINCILIK SAN & TIC LTD, 2012)
To achieve technological capabilities that can lead to sustainable competitive advantage, there is a need for a highly qualified workforce that is capable of innovating and managing technology. Therefore, education on technology and innovation management is increasing in importance, especially for developing countries. Technology and innovation management courses in higher education constitutes the significant part of the formal education in the field, hence the effectiveness of these courses has become a major issue. However in previous literature, several researchers tried to discover the ideal basic characteristics of curricula for technology and innovation management education and particularly for graduate and undergraduate courses in terms of content and theory and practice balance in universities This study aims to explore and reveal the current status of technology and innovation management courses in business administration and engineering faculties, science, technology and social sciences institutes in 95 public universities in Turkey. The findings are evaluated in terms of meeting the required major patterns of courses that are determined based on the theoretical background. Differences are considered as improvement requirements and related recommendations to practitioners are presented. Study reveals that existing courses in the explored higher education institutions are still not sufficient in number and quality to provide the knowledge and skills that create professionals who are competent in technology and innovation management.
Keywords: Technology Management; Innovation; Education; Higher Education; Courses; EDUCATION; BUSINESS; ENTREPRENEURSHIP